Association of IFNA16 and TNFRSF19 Polymorphisms with Intramuscular Fat Content and Fatty Acid Composition in Pigs - Supamit Mekchay; Nanthana Pothakam; Worrarak Norseeda; Pantaporn Supakankul; Tawatchai Teltathum; Guisheng Liu; Watcharapong Naraballobh; Trisadee Khamlor; Korawan Sringarm; Patcharin Krutmuang (Biology, 2022)
Interferon-alpha-16 (IFNA16) and tumor necrosis factor receptor superfamily member 19 (TNFRSF19) are cytokines that may play a role in adipogenesis and fatness. Single nucleotide polymorphisms (SNPs) of the porcine IFNA16 and TNFRSF19 genes were verified and their association with intramuscular fat (IMF) content and fatty acid (FA) composition were evaluated in commercial crossbred pigs. Two non-synonymous SNPs of the porcine IFNA16 c.413G > A and TNFRSF19 c.860G > C loci were detected in commercial crossbred pigs. The porcine IFNA16 c.413G >A polymorphism was significantly associated with stearic acid, total saturated FAs (SFAs), and the ratio of monounsaturated FAs (MUFAs) to SFAs (p < 0.05). Furthermore, the porcine TNFRSF19 c.860G > C polymorphism was found to be significantly associated with IMF content and arachidic acid levels (p < 0.05). The results revealed that porcine IFNA16 and TNFRSF19 polymorphisms are related to IMF content and/or FA composition and affirmed the importance of these cytokine genes as potential candidate genes for lipid deposition and FA composition in the muscle tissue of pigs.